Aquatic metaphors as persuasive and manipulative means in press discourse (based on digital versions of Polish opinion weekly magazines) - Kujawiak, Aleksandra (Zjawiska propagandy i manipulacji w prasie, telewizji, radiu i Internecie, 2022)
In press political discourse, metaphors are often used, thanks to which the sender can impose a specific point of view on the recipient. Using a metaphor, you can create a picture of events, people or phenomena consistent with a given world view option. The popularity of these linguistic means is evidenced by numerous studies on metaphors in the language of politics, among which the following semantic fields are distinguished: war, game, sport, disease, the way from-to, theater/ film or trade. The aim of the article is to analyze the metaphors relating to various forms and properties of water, the so-called aquatic metaphors as persuasive and manipulative means contained in press texts published in 2018–2020 in the weekly magazines “Polityka” and “Sieci”.